Pilot Decontamination over Time Frequency and Space Domains in Multi-Cell Massive MIMO System - Lamiae Hachad; Fatiha Mrabti; Hicham Ghennioui; Mohcine Zouak (Institute of Advanced Engineering and Science, 2018)
In this article, we show that Pilot contamination problem can be seen as a source separation problem using time, frequency, and space domains. Our method capitalizes on a nonunitary joint diagonalization of spatial quadratic time-frequency (STFD) signal representation to identify the desired and interfering users. We first compute the noise subspace from the STFD matrices selected appropriately. Secondly, we use the noise subspace obtained to estimate the Elevation (El) and the Azimuth (Az) angles for which the MUSIC cost function is maximized. Numerical simulations are provided to illustrate the effectiveness and the behavior of the proposed approach.